1956
DOI: 10.1172/jci103262
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-I131 Metabolism in Human Subjects: Demonstration of Insulin Binding Globulin in the Circulation of Insulin Treated Subjects 1

Abstract: In recent tracer studies utilizing I131 labeled insulin, in vivo and in vitro metabolic degradation of the labeled insulin has generally been presumed to parallel the disappearance of protein precipitable radioactivity and the appearance of non-precipitable radioactivity (1, 2). The present investigations were prompted by the paucity of data on the metabolic fate of insulin in human subjects and the need for a more specific identification of insulin-I'13 in blood and tissues than has heretofore been employed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
309
1
16

Year Published

1957
1957
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 795 publications
(336 citation statements)
references
References 14 publications
10
309
1
16
Order By: Relevance
“…It is not surprising that by recent estimates (26) the half life of unlabeled insulin in man is shorter than by previous estimates with insulin-1311 (27,28). Of particular concern are the studies based on the distribution of insulin-131I in animals (29,30) and tissue (31) which related localization of radioactive insulin to the site at which insulin induces its biological effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that by recent estimates (26) the half life of unlabeled insulin in man is shorter than by previous estimates with insulin-1311 (27,28). Of particular concern are the studies based on the distribution of insulin-131I in animals (29,30) and tissue (31) which related localization of radioactive insulin to the site at which insulin induces its biological effect.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin was withheld 24 hours before the experiment, which was performed 3 to 7 days after the surgery. Berson et al (13) showed that injected insulin has a very short half time of disappearance (40 minutes). Davidson et al (14) confirmed this finding in dogs and demonstrated that activity of serum insulin 48 hours after pancreatectomy is not significantly different from zero.…”
Section: Methodsmentioning
confidence: 99%
“…Berson and Yalow [28] reported the presence of circulating insulin-binding immunoglobulins in sera of diabetic patients treated with insulin. It was suggested that insulin resistance and allergies were correlated with the appearance of insulin antibodies.…”
Section: Immunogenic Properties Of Insulinmentioning
confidence: 99%